2006
DOI: 10.1002/pmic.200600207
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins of potential diagnostic value for bovine paratuberculosis

Abstract: Previously we showed that Mycobacterium paratuberculosis culture filtrates (CFs) contain more antigens that react with sera from infected cattle than do cellular extracts of the organism. The goal of the present study was to identify proteins of potential diagnostic value among these CF proteins. Proteins of potential interest were first separated by 2-DE. Roughly 240 CF protein spots were detected on CBB-stained gels using Phoretix 2D software. Of these, 83% reacted with serum from M. paratuberculosis-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…Studies have identified several secreted M. avium subsp. paratuberculosis proteins in culture filtrates, but MAP2872c was not one of them (8), and its involvement in pathogenesis may be worth investigating.…”
Section: Figmentioning
confidence: 99%
“…Studies have identified several secreted M. avium subsp. paratuberculosis proteins in culture filtrates, but MAP2872c was not one of them (8), and its involvement in pathogenesis may be worth investigating.…”
Section: Figmentioning
confidence: 99%
“…paratuberculosis antigens have been investigated for their diagnostic potential in cell-and antibody-mediated assays (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Some of these M. avium subsp.…”
mentioning
confidence: 99%
“…29 Numerous studies have been carried out to identify new antigens that may be used in the currently available and new MAP immunodiagnostic tests. 1,[7][8][9]17,23,24 To date, these recently identified antigens have examined only humoral and not cell-mediated immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of crude antigens has been identified as a problem for the immunological diagnosis of JD in many studies. 1,[7][8][9]23,24,43 There is a need for defined specific antigens that could enable extension of the assay to identify animals likely to be immune and those with a latent infection that will eventually succumb to disease. It may enable identification of sheep that go on to develop a specific lesion type.…”
Section: Discussionmentioning
confidence: 99%